Klasifikasi Risiko Penyakit pada Ibu Hamil menggunakan Metode Modified K-Nearest Neighbor (MKNN) - Yogi Pinanda; Wayan Firdaus Mahmudy; Edy Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Pregnant women need to increase their knowledge to find out how big the level of risk of getting a disease, especially because of the vulnerability of pregnant women. Classification of the level of disease risk in pregnant women is expected to assist users in finding the right solution to overcome it. The classification method used to determine the level of disease risk for pregnant women uses Modified K-Nearest Neighbor (MKNN). Classification of disease risk levels in pregnant women using the Modified K-Nearest Neighbor (MKNN) method can make it easier to detect disease based on existing factors. The Modified K-Nearest Neighbor (MKNN) method is implemented on the expert system inference engine so that conclusions can be drawn based on existing knowledge. The results of the accuracy of the system obtained after testing is 85% which indicates that the Modified KÂ¬-Nearest Neighbor (MKNN) method is suitable for studying the level of disease risk in pregnant women.